Ccn6 Is Required for Mitochondrial Integrity and Skeletal Muscle Function in Zebrafish - Sengupta, Archya; Padhan, Deepesh Kumar; Ganguly, Ananya; Sen, Malini (Frontiers in Cell and Developmental Biology, 2021)
Mutations in the CCN6 (WISP3) gene are linked with a debilitating musculoskeletal disorder, termed Progressive Pseudo Rheumatoid Dysplasia (PPRD). Yet, the functional significance of CCN6 in the musculoskeletal system remains unclear. Using zebrafish as a model organism we demonstrated that zebrafish Ccn6 is present partly as a component of mitochondrial respiratory complexes in the skeletal muscle of zebrafish. Morpholino mediated depletion of Ccn6 in the skeletal muscle leads to significant reduction in mitochondrial respiratory complex assembly and activity, which correlates with loss of muscle mitochondrial abundance. These mitochondrial deficiencies are associated with notable architectural and functional anomalies in the zebrafish muscle. Taken together, our results indicate that Ccn6 mediated regulation of mitochondrial respiratory complex assembly/activity and mitochondrial integrity is important for the maintenance of skeletal muscle structure and function in zebrafish. Furthermore, this study suggests that defects related to mitochondrial respiratory complex assembly/activity and integrity could be an underlying cause of muscle weakness and a failed musculoskeletal system in PPRD.